La escena ubicua: Hacia un nuevo modelo de 'sistema teatral nacional' - Remedi, Gustavo (Latin American Theatre Review, 2005)
By reviewing and discussing the origin and the various stages of the history of Latin American theatre, and more importantly, of the history of the study of theatre and its academic institutionalization, and following Roger Mirza’s and Osvaldo Pellettieri’s notion of national theatrical systems (after which a notion of Latin American theatre followed), in this work I intend to oppose an old triadic national theatrical system (constituted by traditional popular theatricalities, modern European currents and conventions, and commercial ventures) to a new national theatrical system (one that factors in the evolution of Latin American theatre in the 20th C., mass mediated theatricalities, urban spectacles, social and political rituals and performances, and more) that better reflects, and enables us to capture and discuss, both Latin American theatre and Latin American societies and cultures today.(GR)